Synthesis of SnO2 Nanowires Using SnI2 as Precursor and Their Application as High‐Performance Self‐Powered Ultraviolet Photodetectors. Issue 3 (24th November 2017) - Jiang, Jie; Heck, Florian; Hofmann, Detlev M.; Eickhoff, Martin
Abstract : SnO2 nanowires are synthesized by chemical vapor deposition using elemental tin or SnI2 as tin precursors. The latter is found to be more controllable for the synthesis of SnO2 nanostructures. X‐ray diffraction analysis reveals that the SnO2 nanowires exhibit rutile crystal structure. Single nanowire photodetectors are processed, which show high responsivities, high external quantum efficiencies, and fast response times at nominal zero bias. The excellent device performance is attributed to the small size and high crystalline quality of the nanowire. Abstract : In this paper, SnO2 nanowire with high crystalline quality was synthesized by using SnI2 as precursor. An ultraviolet photodetector with high spectral responsivity of 2.33 × 10 5 AW −1, high external quantum efficiency of 1.14 × 10 8 %, and fast response time of less than 0.3 s at a nominal zero set bias was fabricated.